The Existence Of Al-Madaris Terbangan Music In Pladen Village, Jekulo District, Kudus Regency - Wahyu, Muhammad Panji; Sinaga, Syahrul Syah (Universitas Negeri Semarang, 2021)
The existence of Al-Madais' terbangan music group in Pladen Village cannot be separated from the motivation of its members to preserve the terbangan music as a means of da'wah and worship. Despite the limited time, facilities, and infrastructure as well as knowledge and skills, the group still strives to preserve Islamic culture amid the fast growth of the modern era. Therefore, the purpose of this study is to describe the existence of Al-Madais' terbangan music arts. This study uses a qualitative descriptive method, with data collection techniques through observation, interviews, and documentation. Meanwhile, the data analysis technique was carried out by reducing, presenting, and verifying data. The results of the study indicate that the existence of the Al-Madais terbangan music group, in terms of the adopted strategy, one of which is good management. Then in terms of consistency, it is carried out with the existence of an organizational structure, regeneration process, and mundane rehearsal. The innovation is carried out by imagination and creativity without leaving its cohesiveness and characteristics. The acknowledgment of the Al-Madais existence is proved by performing at various events and support from the government.